Menikah adalah Ibadah: Peran Agama dalam Mengkonstruksi Pengalaman Melajang di Indonesia - Karel K. Himawan (Jurnal Studi Pemuda, 2020)
Religion plays a major role in the lives of most Indonesians. While most religions favour marriage, little is known regarding how religion shapes the singleness experience, especially from the Indonesian perspective. The study aims to explore whether and how religion constructs the meaning of singleness and contributes to the quality of life of Indonesian unmarried individuals. Multistage mixed-methods study was employed to answer the research questions through two stages. Stage one was an online survey to 635 participants (Mage = 31.49; SD = 5.49) across three groups (single, single in a relationship, and married). Stage two utilised interviews to 40 unmarried participants (Mage = 33.14; SD = 4.04). The survey results suggest that as a group, single individuals indicated lower levels of quality of life compared to married people. Among single participants, multivariate analysis suggests that religiosity significantly increases life satisfaction, but does not reduce loneliness. Three themes emerged regarding the role of religion in constructing the meaning of singleness: singleness as a God-willed temporary period, a period to embrace life outside marriage, and a period where conservative socio-religious norms are negotiated with contemporary values. The study highlights the complex and pivotal role of religion in the Indonesian singleness experience.